Family Caregivers and Suicide Prevention: A Needs and Assets Assessment in Egypt - Allam, Lina Osama (AUC Knowledge Fountain, 2026)
In the Arab world, suicide prevention is shaped by cultural stigma and religious beliefs, shaping both help-seeking behaviors and the design of support systems. Family caregivers play a vital role in suicide prevention but often face significant emotional and logistical burdens. This study is the first known scholarly effort in Egypt to examine the intervention needs of these caregivers. It explored three key questions: the roles and challenges of caregivers supporting individuals with suicidal thoughts or behaviors; the availability of clinical and community-based resources; and the characteristics of future interventions to support them. A total of 92 mental health professionals participated via an online survey, representing diverse specializations including psychiatry, clinical psychology, and counseling psychology. Respondents described family members engaging in universal caregiving roles, such as attending to basic needs and safety planning, along with a distinctive emphasis on religious guidance due to religious prohibitions of suicide. Reported family caregiver challenges spanned ecological levels, including patient issues, caregiving environment, family attitudes towards services, mental health infrastructure, and culture and policy. While professionals offered practical, informational, empathetic, and motivational support, gaps remain in community-based services such as case management, peer support, and respite care. Although respondents favored future interventions designed and delivered in clinical settings by professionals with mental health or social services expertise, they also welcomed initiatives from governmental, academic, religious, and nonprofit sectors. The study concludes with a set of interdisciplinary interventions involving caregivers in suicide prevention efforts at universal, selective, and indicated levels, and calls for future research that centers caregivers’ voices, especially in suicide bereavement.